Barragens em sequência: composição e distribuição do Ictioplâncton em um complexo energético de um rio Neotropical - Ticiani, Douglas (2018)
Run of River hydroelectric systems, beyond fragments aquatic environments, drastically reduced as flow discharges in the Reduced Flow Stretch (RDS). The objective of this study was to evaluate the influence of TVR formation and environmental variables on composition and spatial distribution of eggs and larvae, in dams cascade operating with free threshold and under the Run of River system. Fortnightly nocturnal samplings were carried out between October/2016 and January/2017, in four points of influence area of the Rio das Antas Energy Complex, Patos Lagoon ecoregion. The ichthyoplankton was collected with conical-cylindrical networks, in three sections of the river and by a light trap per point. The eggs were quantified, while larvae were identified using the sequence regression development technique, framed in larval periods (larval yolk, pre-flexion, flexion and post-flexion) and juvenile. Were collected 5,681 eggs, 2,124 larvae and 43 juveniles, belonging to 25 taxonomic groups. Small species, sedentary and without parental care (small characids) had the highest total abundance and density. Significant spatial differences were identified in egg and larval densities, as well in the stages of ontogenic development, influenced by flow, temperature, pH and dam-free river stretch. The higher density of upstream larvae and the greater species richness downstream of the complex, indicate disruption in the natural processes of drift and the displacement of many species in the upstream direction. Higher flow rates positively influenced the use of RDS as spawning sites.